Evolution and Implications of Changes in Seismic Load Codes for Earthquake Resistant Structures Design - Abdul Kadir; Ahmad Syarif Sukri; Nini Hasriani Aswad; . Masdiana; . Nasrul (Civil Engineering Journal, 2024)
Seismic load is a critical load that can trigger damage or collapse of structures, especially in earthquake-prone areas. The susceptibility of structures to seismic loads is influenced by factors related to soil characteristics and structural behavior. This paper comprehensively examines the development of Indonesian seismic code design parameters and their comparison with the current seismic code. The results of the analysis showed that the design spectral acceleration of short-period AD and long-period A1 SKBI 1987 and SNI 2002 increased with increasing PGA values, with a consistent pattern of SC < SD < SE. Unlike the previous two codes, design spectral acceleration AD and A1 SNI 2012 and SNI 2019 experience fluctuations in all types of soil. The ratio design spectral acceleration of AD and A1 SNI 2019 to KBI 1987 and SNI 2002 varies; there are up, fixed, and down for SC, SD, and SE soil conditions. The ratio of design spectral acceleration AD and A1 SNI 2019 to SNI 2012 designs also varies; this condition is due to changes in site coefficients. There were significant changes to the SKBI 1987 and SNI 2002 structural systems, especially the low and medium seismic levels. The increase in the seismic influence coefficient ratio of some cities varies for each type of soil and code. The increase in the 1970 PMI seismic coefficient was < 30% for all soil types, and the highest percentage increase occurred in SC soil types. The increase in seismic coefficient in SKBI 1987, SNI 2002, and SNI 2012 is more dominant in SE soil types. Doi: 10.28991/CEJ-2024-010-01-04 Full Text: PDF